Analysis Of Directive And Expressive Speech Acts Used By Both Teacher-Learners During Classroom Interactions Found In Movies Entitled "Dangerous Minds", "The Ron Clark Story", And "Facing The Giants" - Puspitasari, Novi Fitri; , Agus Wijayanto, Ph.D; , Dr. Dwi Haryanti, M.Hum (2015)
ABSTRACT Novi Fitri Puspitasari. S200130048. ANALYSIS OF DIRECTIVE AND EXPRESSIVE SPEECH ACTS USED BY BOTH TEACHER-LEARNERS DURING CLASSROOM INTERACTIONS FOUND IN MOVIES ENTITLED DANGEROUS MINDS, THE RON CLARK STORY, AND FACING THE GIANTS. Thesis. Muhammadiyah University of Surakarta. 2015. The use of speech acts in communication is considered successful if the interlocutor is able to understand the speakers' messages. The current study focused on directive and expressive speech acts, aimed at identifying its types, identifying its directness levels and identifying its pragmalinguistics variations which were found in teacher-learners interactions. The object of the study was the interactions between teachers and learners in which the directive and expressive speech acts frequently occur. The sources of the data were three drama movies entitled 'Dangerous Minds', The Ron Clark Story' and 'Facing the Giants'. The movies were selected because the most of its settings took place in classroom. From the data analyzed, the directive speech acts - commanding, requesting, suggesting - the most commonly found was commanding and the least found was suggesting. In terms of the expressive speech acts - thanking, apologizing, complimenting - the dominant discovered was complimenting and the least discovered was thanking. The direct strategy is the most compare those of indirect strategy. With respect to pragmalinguistics variations, there were 8 data of syntactic downgraders and 14 data of lexical/phrasal downgraders. The result of this study has contribution to the theory of speech acts. In addition, it can provide the information of how improve the strategy for making successful communication. Keywords: directive, expressive, directness levels, pragmalinguistics variations, speech acts